The calmodulin content of normal and leukaemic lymphocytes. Issue 9 (September 1985) - MacNeil, sheila; Dawson, Rebecca; Tucker, William F. G.; Clegg, Alan; Platts, Andrew; Rees, Robert C.
Abstract : Normal human peripheral blood mononuclear cells (PBMC) and leukaemic cell lines (three of human and one of gibbon origin) were found to contain similar levels of calmodulin (CaM) when expressed relative to the total cell protein. Two of the cell lines examined further were found to contain much higher amounts of CaM per cell (up to 5-fold) than PBMC but this was readily explained by their much greater cell size. Variations in CaM levels were noted during culture of both PBMC and leukaemic cells which were apparently independent of the percentage of cells undergoing active division in these cultures. These results do not support, the contention that transformed cells contain a higher proportion of CaM than normal cells.